Antibacterial, Antidiabetic and Brine Shrimp Lethality Activities of Some Selected Medicinal Plants from Kavrepalanchok District of Nepal - Sharma, Khaga Raj; Kharel, Rupak (Journal of Institute of Science and Technology, 2019)
The methanol extracts of nine medicinal plants collected from Kavrepalanchok district of Nepal were subjected to their potential bioactivity viz. antibacterial, antidiabetic and toxicity tests. Antibacterial property of the extracts was evaluated against Gram-positive and Gram-negative bacteria by agar well diffusion method and antidiabetic activity was investigated by α-amylase inhibition assay. The toxicity of plant extracts was assessed by brine shrimp lethality test. All the nine different plant extracts showed antibacterial activity with the zone of inhibition (ZOI) ranging from 5 to 35 mm. Among the studied plant extracts, Psidium guajava showed the highest ZOI against Salmonella typhi (35 mm) while Melia azedarach was most effective against Staphylococcus aureus (22 mm). The percentage of α- amylase enzyme inhibition was found up to 88.56 ± 3.50 in dose dependent manner. The enzyme inhibitory concentration IC50 value of standard, acarbose was 166.01 μg/mL while the most effective anti-diabetic plant extract of Utrica dioica has 186.67 μg/mL. Moreover, various plant extracts depicted various levels of toxic activities; Curcuma longa demonstrated significant toxicity to Artemia salina with LC50 value 62.10 μg/mL, while Agerantina adenophora, P. guajava and M. azedarach showed moderate toxicity with 103.77, 109.37 and 383.58 μg/mL, respectively.